Nilai Sosial Keberagamaan Islam dalam Moderasi Beragama - Wahyudin, Wahyudin; Taufiq, Ahmad; Islamy, Athoillah (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2021)
This study aims to identify the social values of Islamic religiosity in the indicators of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia. This research center uses a normative-philosophical approach with analytical theory in the form of a Prophetic Social Science paradigm that was initiated by Kuntowijoyo. The results of the study show that there are various prophetic social values of Islam contained in the four indicators of religious moderation in Indonesia. First, the value of transcendence in the indicator of tolerance as a mindset and social attitude to realize an attitude of religious moderation, both in the context of inter-religious and intra-religious life. Second, the value of humanization in moderation indicators in the form of an attitude of national commitment and accommodative to local culture can take the form of various forms of benefit in order to maintain nationalism and plural local wisdom in Indonesia. Third, the value of liberation in indicators of anti-radicalism attitudes as an effort to realize the framework of realizing a safe and peaceful life.